The Impact on Applying Numbered Head Together (NHT) as Teaching Strategy to Increase the Students’ Reading Comprehension - Lely, Ledy Nur; Hamer, Welliam; Aulia, Dea Ratna (Journal of English Education Studies, 2021)
The purpose of this study was to determine the impact on applying the Numbered Head Together (NHT) strategy on eighth-grade students' reading comprehension of recount material at SMPN 10 Kota Serang. For the study, the researchers conducted quantitative research with a true experimental design. The participants in this study were eighth grade students of SMPN 10 Kota Serang. Cluster random sampling was used to choose the sample for this study. There were 30 students in each of the two classes participated in this study: VIII B as the experimental class and VIII G as the control class. The experimental class was instructed using the NHT strategy, while the control group was instructed using the lecturing technique. The data were gathered by pre- and post-tests, and the hypothesis was tested by using the t-test procedure. The t-test calculation revealed that t-count (9.22) was higher than t-table (2.00) with a significance of 0.05. This indicates that the alternative hypothesis (Ha) has been accepted. It can be determined that applying the NHT strategy had a substantial impact on students' reading comprehension of recount text in eighth grade at SMPN 10 Kota Serang.